1996
DOI: 10.1007/bf01209124
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and clinicopathological correlates of serum anti-p53 antibodies in breast and colon cancer

Abstract: The humoral immune response to p53 was determined in 54 individuals with colon or breast cancer and 50 healthy subjects, in an attempt to better understand the origin and significance of anti-p53 serum antibodies. The presence of anti-p53 antibodies in serum was determined by enzyme-linked immunosorbent assay using purified recombinant human p53, and results were validated by immunoprecipitation of radiolabelled p53. Immunohistochemical analysis of 28 tumours was performed to detect the accumulation of p53 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…21,22 In the current study, the proportion (13%) of seropositive patients is consistent with a previous report on CRC 15 but represents a lower figure than other studies reporting positivity rates varying from 18 to 32%. 16,18,20,[23][24][25] In a previous study, 26 we reported that Taiwan had the lowest frequency of p53 mutations (31%) and the highest frameshift mutation rates among various population studies, which agrees with half of the CRC patients with a p53 mutation in the tumor having circulating p53-Abs. 3 In accordance with other studies, 18,23,25-27 in our series, we found no correlation with demographic or clinicopathologic features, except for tumor location and nodal status of the tumor.…”
Section: Discussionsupporting
confidence: 60%
“…21,22 In the current study, the proportion (13%) of seropositive patients is consistent with a previous report on CRC 15 but represents a lower figure than other studies reporting positivity rates varying from 18 to 32%. 16,18,20,[23][24][25] In a previous study, 26 we reported that Taiwan had the lowest frequency of p53 mutations (31%) and the highest frameshift mutation rates among various population studies, which agrees with half of the CRC patients with a p53 mutation in the tumor having circulating p53-Abs. 3 In accordance with other studies, 18,23,25-27 in our series, we found no correlation with demographic or clinicopathologic features, except for tumor location and nodal status of the tumor.…”
Section: Discussionsupporting
confidence: 60%
“…Presence of anti-p53 serum antibodies is regarded as a bad prognostic factor in breast and head and neck cancer, or as an increased risk for relapse but not death in ovarian and colon cancer (Schlichtholz et al, 1992;Houbiers et al, 1995;Angelopoulou et al, 1996;Bourhis et al, 1996;Coomber et al, 1996). As previously mentioned, eight patients of our series operated for HCC had antip53 serum antibodies, and at least one factor of bad prognosis as defined by the experience of different groups (Akashi et al, 1991;Yamashita et al, 1991;Bismuth et al, 1993;Ganne-CariŽ et al, 1996).…”
Section: Discussionmentioning
confidence: 48%
“…More recently, serum antibodies reacting with the p53 protein have been detected in cancer patients with a variety of neoplasms (Schlichtholz et al, 1992;Angelopoulou et al, 1994Angelopoulou et al, , 1996Volkmann et al, 1993;Houbiers et al, 1995;Lubin et al, 1995a, b;Bourhis et al, 1996;Coomber et al, 1996;Gadducci et al, 1996;Ryder et al, 1996;Wild et al, 1995). A prerequisite for a B-cell response seems to be the accumulation in the tumour of a mutant or, less frequently, a wild-type p53 protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…41 Of the individuals with a humoral response to p53, most have antibodies against the immunodominant amino-terminal and carboxy-terminal regions. [42][43][44][45][46] The secondary structure of these regions remains unchanged in mutant forms of the protein, suggesting that the immune response is more likely to be due to accumulation of the protein than to the appearance of novel antigenic determinants by mutation. Several other studies have identified patients with anti-p53 antibodies but no identifiable accumulation of p53 in their tumors.…”
Section: Discussionmentioning
confidence: 99%